1998
DOI: 10.1094/pdis.1998.82.1.129d
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Plasmodiophora brassicae on Cabbage in Eastern North Carolina

Abstract: Clubroot, caused by Plasmodiophora brassicae Woronin, has occurred for at least 50 years in three counties in northwestern North Carolina, but has not been reported previously from eastern North Carolina, where most commercial cabbage is produced. In the fall of 1995, clubroot was observed in a direct seeded, commercial cabbage field in Plymouth, NC. Diseased cabbage plants were stunted and roots exhibited clublike swellings. Clubs were randomly harvested from roots of five plants to obtain a composite isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The clubroot pathogen was identified as Plasmodiophora brassicae Woronin based on its morphological and pathological characteristics, which were consistent with those described by Buczacki (1979). It was reported that P. brassicae causes clubroot of crucifers (Buczacki, 1979; Cubeta et al, 1998; Linnasalmi and Toiviainen, 1991). The disease has been a major problem in areas where Chinese cabbage and some other cruciferous crops are cultivated in Korea (Cho et al, 2003; Kim and Oh, 1997).…”
mentioning
confidence: 99%
“…The clubroot pathogen was identified as Plasmodiophora brassicae Woronin based on its morphological and pathological characteristics, which were consistent with those described by Buczacki (1979). It was reported that P. brassicae causes clubroot of crucifers (Buczacki, 1979; Cubeta et al, 1998; Linnasalmi and Toiviainen, 1991). The disease has been a major problem in areas where Chinese cabbage and some other cruciferous crops are cultivated in Korea (Cho et al, 2003; Kim and Oh, 1997).…”
mentioning
confidence: 99%